Tectonic setting and timing of the final Deccan flood basalt eruptions - Hooper, Peter; Widdowson, Mike; Kelley, Simon (Geology, 2010)
The role of extensional tectonics in the generation of basaltic melt and eruption of continental flood basalts is controversial, and yet it remains crucial to understanding the origin and cause of these large-volume eruptions. Establishing the timing of lithospheric extension, continental rifting, and the onset of continental flood basalt volcanism is therefore of importance to petrogenetic models. Detailed mapping along the Mumbai coast, India, reveals three chemically distinct sets of dikes, which, together with high-precision 40Ar/39Ar dating, demonstrate the temporal relationship between lithospheric extension and Deccan volcanism. The east-west extension evident along the west coast of India, which led to the separation of the Seychelles from the Indian plate, only began during the final phases of the basalt eruptions, and cannot have initiated the large-volume eruptions of the Deccan flood basalt province. © 2010 Geological Society of America.